PENGARUH KEGIATAN INDUSTRI TERHADAP KUALITAS PERMUKIMAN KOTA BITUNG - Sakul, Fianna G.; Tilaar, Sonny; Rondonuwu, Dwight M. (MEDIA MATRASAIN, 2021)
The development of an area can provide various kinds of influence on people's lives. Basically, the development of settlements in both urban and rural areas is to realize livable, safe, comfortable, peaceful and prosperous urban and rural conditions, but if the settlements are not properly facilitated or the settlement facilities are not functioning properly or if the settlements are located around industrial areas as well as economic and service centers, it can affect the quality of a settlement.. However, from the various positive influences obtained from industry, there are also negative influences such as the effect on the quality of settlements because in addition to producing various products and various manufactured objects, industrial activities can also produce air and noise pollution caused by industrial production equipment and tools. -Industrial transportation means entering and leaving the industry. Bitung City is one of the industrial cities in North Sulawesi Province which is divided into various types of industries, but most of them are located very close to residential areas which allow the residential area to receive various influences from all activities in the surrounding industry. The purpose of this study is to identify the condition of settlements in urban villages that are close to industry, and to analyze the influence of industrial activities on the quality of settlements in areas close to industry in Bitung City. The analytical method used is the path analysis method by taking data from a questionnaire. Then the results of the correlation test show that there is a relationship between industrial activities on the quality of settlements and the results of the regression test show that if there is an increase in the quality of industrial activities, it will affect the value of the quality of settlements positively.